Clinical importance of sternalis muscle and anatomical variations: a systematic review of literature - Oliveira, Luana Agapito de (2017)
The presence of sternal muscle is an anatomical variation, located above the sternum and adjacent structures, and its function is not fully defined. In the literature, there are more reports of anatomical studies of the sternal muscle than clinical implications of its presence. The objective of this study was to analyze descriptions about anatomical variations of the sternal muscle and understand the clinical importance of this knowledge. Articles in Portuguese and English, indexed in the databases PubMed and SciELO, from 1867 to 2016, were evaluated. The types of anatomical variants of sternal muscle, its origins and insertions, innervation and blood supply were observed. After that, was brought the clinical importance of knowledge of this variation. The sternal muscle has several dimensions and inserts, making difficult to determine its function. Due to its parasternal location in imaging studies it may be seen as an abnormal bulge in the breast region and confused with a tumor. The discovery of this variation before thoracic surgical procedures avoids possible complications, enabling its use as a muscle flap in reconstructive surgery after mastectomy or improving the aesthetic result of breast augmentation providing extra covering for the prosthesis. The knowledge about this anatomical variation is quite relevant, because the perception of the existence of the sternum muscle and its variations is related to important clinical implications in breast and chest surgeries.